The effect of quizlet application towards students’ vocabulary mastery at the Eighth Grade of SMP-IT Mathla’ul Anwar Malingping Lebak, Banten in the Academic Year 2023/2024 - Dela Maulida; Ade Sudirman; Tatu Munawaroh (CV. Kurnia Grup, 2024)
The research paper aims to investigate the effect of quizlet application towards students’ vocabulary mastery at the eighth grade of SMP-IT Mathla’ul Anwar Malingping Lebak, Banten. This research was conducted for five weeks at the class eighth grade of SMP-IT Mathla’ul Anwar Malingping. The method of the research was used quantitative approach and the research design used quasi experimental design and and purposive sampling. The population of this study was 38 students. The sample of this study was 38 eighth grade of SMP-IT Mathla’ul Anwar Malingping, which were divided into experimental and control groups, and each group consisted of 19 students. To collect data, each group was given a pre-test and post-test. The data analysis technique used paired sample t-test which is calculated using SPSS 25. The results of this research of the post-test of the experimental class 88.42 and the control class 84.42 then, this results of the t-test obtained a significance value of 0.000 ≤ α = 0.05. These results show that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. So, this research is a significant effect on vocabulary mastery by using quizlet application.